2021
DOI: 10.1097/md.0000000000025386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traditional Chinese medicine emotional therapy on post-stroke depression

Abstract: Background: Post-stroke depression has seriously affected the rehabilitation and quality of life of patients, and there is no reliable treatment plan at present. Nursing plays an important role in the recovery of patients, some studies have pointed out that traditional Chinese medicine emotional therapy has advantages in improving post-stroke depression and promoting rehabilitation, but it is lack of evidence-based basis. The purpose of this study is to systematically evaluate the effect of tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Thus, patients recover faster, with fewer complications and higher satisfaction. Yang et al [33] demonstrated that EBN in acute stroke patients can effectively comfort their psychological and spiritual levels, thus reducing their anxiety, depression, and other negative emotions, which is consistent with our research results. In the report of Zhang et al [34], the application of EBN in patients with lung cancer radiotherapy and chemotherapy can not only significantly improve their psychological state but also enhance their QoL, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, patients recover faster, with fewer complications and higher satisfaction. Yang et al [33] demonstrated that EBN in acute stroke patients can effectively comfort their psychological and spiritual levels, thus reducing their anxiety, depression, and other negative emotions, which is consistent with our research results. In the report of Zhang et al [34], the application of EBN in patients with lung cancer radiotherapy and chemotherapy can not only significantly improve their psychological state but also enhance their QoL, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Most scholars believe that similar to typical asthma, on the one hand, the patient's own congenital constitution, “genetic quality,” immune status, mental state, health status, and other subjective factors, in addition to allergens, bacterial and viral infections, changes in climate, excessive exercise, occupational environment, and food and drugs, may be factors that promote the occurrence, and the pathogenesis of CVA is complex and clinically unclear, and studies have found that CVA and typical asthma have similar pathological features [ 10 ], such as the presence of specific inflammatory patterns and airway remodeling [ 12 ]. CVA patients only cough without wheezing, and there are nowadays three explanations for this phenomenon: the degree of ASR is lower in CVA compared to asthma, the wheezing threshold of CVA causing wheezing, and the coughing receptor sensitivity is also increased [ 13 ]. The bronchoconstriction reflex and the cough reflex are two interrelated and independent types of reflexes, and most of their cough receptors are present in the patient's airways, which are physically stimulated by the deformation of the airways due to bronchoconstriction and chemically stimulated by inflammatory mediators [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety was measured by Zung’s self-rating anxiety scale (SAS), which includes 20 items using a 4-grade scoring method with a maximum score of 100 points. 13 , 14 Usually, SAS score has the 4 categories: no anxiety (<50), mild anxiety (50–59), moderate anxiety (60–70) and severe anxiety (>70). A greater score indicates the higher degree of anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…The SDS also employs a 4-grade scoring method with a maximum score of 100 points. 14 A higher SDS score indicates a severe depression, which was classified as: <50, no depression; 50-59, mild depression; 60-70, moderate depression; >70, severe depression. 15 Neuropsychiatric Disease and Treatment 2022:18 https://doi.org/10.2147/NDT.S377340…”
Section: Instrumentsmentioning
confidence: 99%